The Utilization of Artificial Intelligence in the Educational Communication Process at Bandung 2 Senior High School - Olih Solihin; Yasundari Yasundari; Yuni Mogot; Dessy Angelia Syawalani; Mohammad Hardiansyah (Universitas Dian Nuswantoro, 2026)
The rapid development of artificial intelligence (AI) has significantly influenced educational practices, particularly in shaping communication processes between teachers and students. This study aims to examine the utilization of AI in learning activities and its impact on educational communication at SMA Negeri 2 Bandung. Specifically, it focuses on how AI affects teacher–student interaction, communication patterns, and the pedagogical role of AI in the classroom. This study employed a convergent mixed-methods design, integrating quantitative and qualitative data. Quantitative data were collected through a survey of 187 students, while qualitative data were obtained from in-depth interviews with two teachers and five students. The findings indicate that approximately 89% of students use AI regularly or occasionally, primarily for academic purposes, with ChatGPT as the most frequently used platform. The results reveal that AI enhances students’ access to information and learning efficiency; however, it also reshapes communication patterns. Students tend to reduce direct consultation with teachers, shifting toward more independent, AI-assisted learning. At the same time, qualitative findings show that teachers remain essential in guiding interpretation, fostering critical thinking, and maintaining meaningful educational interaction. This study highlights a key paradox: while AI increases functional learning efficiency, it may weaken dialogic communication and critical engagement if not properly guided. Therefore, the integration of AI in education should emphasize teacher supervision, digital literacy, and human-centered communication practices. Keywords: Artificial Intelligence; ChatGPT; Digital Literacy; Educational Communication; Learning Process